Identifikasi Telur Cacing Ascaris lumbricoides Pada Sumber Air Di Madang Dalam, Sekip Jaya - sitindaon, Rina SE; Ernia, Rima; Tumanggor, Lisnawati (JURNAL KESEHATAN TERAPAN, 2022)
Ascaris lumbricoides is a roundworm that belongs to the class of intestinal nematodes that are mostly found in tropical and subtropical areas where the local conditions are suitable for breeding. The prevalence of worm egg infection is generally transmitted through food, drink and water sources that are always used for daily needs such as water for drinking, washing, cooking and bathing. This study aims to identify Ascaris Lumbricoides worm eggs in water sources with samples obtained from several water sources in Madang Dalam. Experimental research method with qualitative laboratory examination with Flotation method to identify worm eggs. The population of all water sources in Madang Dalam, Sekip Jaya. Primary data is data generated from samples of water sources. The results of the research conducted showed negative results containing worm eggs, so the water source was safe to use. Keywords: Ascaris lumbricoides, Water sources, Worm eggs